Social Assistance Policy: an assessment of municipal management based on the SUAS Census - Caetano, Marina; Guimarães, Gleny Terezinha Duro; Fiorotti, Marlene Rosa de Oliveira (Argumentum, 2021)
This article reflects on the city management of the Unified Social-Assistance System (SUAS), based on the analysis of data reported in the SUAS Census in 2016 and 2017. Using these documents as a reference point, the present study is based on documentary research with a qualitative approach and is a case study based on three cities of in the state of Rio Grande do Sul. The categories analyzed are as follows: administrative management structure, level of social protection, socio-assistance surveillance structure, referral team, SUAS work and budget management, management of CadÚnico and the Bolsa Familia Program, and continuing education. It concludes that there have been breakthroughs in ​​technical support to municipal workers and managers by the State, but it also points out the dismantling of the SUAS management, which has repercussions for the quality of socio-assistance services offered to the population.